Smart Address: Art Deco, Style Moderne and Their Contemporaries in Toronto. THE MARKET GALLERY AND THE TORONTO ARCHITECTURAL CONSERVANCY, TORONTO - Gomoll, Wendy (Archivaria, 2014)
Smart Address: Art Deco, Style Moderne and Their Contemporaries in Toronto. THE MARKET GALLERY AND THE TORONTO ARCHITECTURAL CONSERVANCY. Mounted at the Market Gallery, St. Lawrence Market, Toronto. 26 October 2013 to 25 January 2014. Curated by ALEC KEEFER